431 Histopathological results after risk-reducing bilateral salpingo-oophorectomy in BRCA1/2 mutation carriers: single center experience. (4th December 2020) - Ehmann, Sarah; Ramspott, Jan Philipp; Bois, Andreas du; Harter, Philipp; Schneider, Stephanie; Baert, Thaïs; Traut, Alexander; Heikaus, Sebastian; Pauly, Nina; Ataseven, Beyhan
Abstract : Introduction/Background: Women with BRCA1 and 2 mutation are at increased risk for developing ovarian and breast cancer. Risk-reducing salpingo-oophorectomy (RRSO) can be offered to these women to minimize their risk. The pathologic sectioning and extensively examining the fimbriated end (SEE-FIM)-protocol is applied by the pathologist to detect premalignant lesions and early stage cancer. The rate of occult serous tubal intraepithelial carcinoma (STIC) lesions and ovarian cancer in this RRSO-population ranges between 0.6–10.0%. The prevalence of pathogenic lesion in RRSO is clinically relevant. Methodology: All consecutive patients with a pathogenic mutation (BRCA1/2, RAD51C, Lynch gene mutation, PALB2, BRIP1) who underwent RRSO between 11/2011 and 05/2020 in our Department of Gynecologic Oncology at Kliniken-Essen-Mitte were assessed from our prospectively managed database. All specimens were analysed according to the SEE-FIM-protocol. Results: In total, 241 women underwent RRSO of whom 216 were included in the final analysis. Median age was 48 years (range 22–79). 134 (62.0%) women had breast cancer in their past medical history. Family history showed breast and ovarian cancer in 104 (48.1%) and 49 patients (22.7%). BRCA1 mutation was underlying in 121 (56.0%) patients, whereas 64 (29.6%) patients had a BRCA2 mutation, 22 women (10.2%) an unknown mutation status. Nine patients (4.2%) presented with a RAD51C, Lynch gene, PALB2, or BRIP1 mutation. Most patients (99.1%) underwent minimal invasive surgery. Incidental findings of a STIC lesion and/or ovarian cancer was detected in 7 (3.2%) and 5 (2.3%) patients. Median age of those 12 women was 56 years (range 44–79) and all underwent a staging surgery. Final histopathological results showed high grade serous ovarian cancer in 5 patients: FIGO IA (n=1), FIGO IB (n=1), FIGO IC (n=1), FIGO IIA (n=1), FIGO IIIC (n=1). Seven women had STIC lesions. All patients with ovarian cancer had a BRCA1 mutation and one patient even had a BRCA1 and RAD51C mutation. Of all STIC patients five (71.4%) had a BRCA1 and two (28.6%) had a RAD51C mutation. Conclusion: Our results of incidental STIC/ovarian cancer findings confirm the results published in the literature. RRSO is highly recommended in mutation carriers. Genetic counselling and testing need to be routinely offered to family members of mutation gene carriers. It is from tremendous importance to raise awareness that in women at high risk, the development of premalignant neoplasms and malignancies can be prevented. Timing of RRSO should be independent of age and promptly after completion of family planning. Disclosures: SE received non-financial support from Tesaro, outside the submitted work. JPR has no conflict of interest to declare. AdB reports personal fees from Roche, Astra Zeneca, Tesaro, Clovis, Pfizer, Genmab, Pharmar, and Biocad, outside the submitted work. PH reports grants and personal fees from Astra Zeneca and Roche, personal fees from Sotio, grants and personal fees from Tesaro and GSK, personal fees from Stryker, Zai Lab, and MSD, grants from Public funding (DKH, DFG, EU), personal fees from Clovis, andImmunogen, grants from Boehringer Ingelheim, Medac, and Genmab, outside the submitted work. SS reports personal fees from Roche, Astra Zeneca, personal fees and travel grants from GSK/Tesaro, personal fees from Clovis and travel grants from Pharmamar, outside the submitted work. TB has been an advisor for Tesaro and received research grant from Amgen, non-financial support from Amgen, MSD, Roche, and Tesaro, outside the submitted work. AT, SH, NP have no conflicts of interest do declare. BA reports personal fees and non-financial support from Roche, personal fees from Amgen and Astra Zeneca, personal fees and non-financial support from Tesaro, personal fees from Clovis and Celgene, non-financial support from PharmaMar, outside the submitted work.